ナンキョク タイリュウケン ノ エアロゾル エンチョク ブンプ ト ソノ キセツ ヘンカ - 原, 圭一郎; ハラ, ケイイチロウ; 長田, 和雄; オサダ, カズオ; 西田, 千春; ニシダ, チハル; 山内, 恭; ヤマノウチ, タカシ; 林, 政彦; ハヤシ, マサヒコ; Hara, Keiichiro; Osada, Kazuo; et al. (2010)
P(論文) 第46次日本南極地域観測隊において,係留気球を用いたエアロゾル鉛直分布観測を南極昭和基地で実施した.CN数濃度の季節変化は夏に極大を示す傾向があったが,微小(D_p>0.3 μm)～ 粗大(D_p>2.0 μm)粒子数濃度は夏季に低く,冬季に高くなっていた.CN濃度変化の幅は,地上付近では30-2200 cm^<-3> の範囲で変化していたが,自由対流圏(>1500 m)での変化幅は7-7250 cm^<-3> となっていた.夏季の自由対流圏下部では,新粒子生成による高CN数濃度が観測された.地上での新粒子生成イベントが確認されるよりも高い頻度で,南極域の自由対流圏下部において新粒子生成が起きていることが示唆される.また,個別粒子分析の結果から,冬季には,海氷上で起こる組成分別過程によりMgが濃縮されている海塩粒子と,NO_3^<-> やSO_4^<2-> により変質した粒子が多かった.海塩の組成分別過程によるMg濃縮海塩粒子とその変質過程が,冬季のエアロゾル粒子の吸湿特性に大きな影響を及ぼしていることが示唆される.Hara et al.(2010a)で報告されているヘイズ現象は,境界層だけではなく,自由対流圏でも観測されることがあった. Tethered balloon-borne aerosol measurements were carried out at Syowa Station, Antarctica during the 46th Japanese Antarctic Research Expedition. CN concentration had a maximum in the summer, whereas the number concentrations of fine particles (D_p>0.3 μm) and coarse particles (D_p>2.0 μm) increased during the winter-spring. The range of CN concentration was 30-2200 cm^<-3> near the surface (surface-500 m) and 7-7250 cm^<-3> in the lower free troposphere (>1500 m). During the austral summer, higher CN concentration was often observed in the lower free troposphere. Frequent appearance of higher CN concentration in the free troposphere relative to the surface measurements strongly suggests that new particle formation in the Antarctic regions occurs in the lower free troposphere. Single particle analysis indicated that most of the aerosol particles during the winter were composed of Mg-enriched sea-salt particles originated from sea-salt fractionation on the sea-ice and their modified particles by NO_3^<-> and SO_4^<2->. This suggests that sea-salt fractionation on sea-ice and modification of sea-salt particles were affected greatly by aerosol hygroscopicity during the winter. Antarctic haze layer was observed not only in the boundary layer but also in the lower free troposphere. departmental bulletin paper